PENGARUH PEMBERIAN SUPLEMEN MINERAL ZAT BESI (Fe) TERHADAP KADAR HEMOGLOBIN (Hb) ATLET SEPAKBOLA RAJAWALI KOTA PADANG - Anggri Anggri; Pudia M Indika (JURNAL STAMINA, 2019)
This study aims to determine the effect of iron supplement to hemoglobin values, type of quasi-experimental research with two group pree test post test design. The research subjects were 16 Rajawali Padang Soccer School. Subjects given iron supplement merk Sofero 16 times, values of hemoglobin were taken after and before treatment using a easy touch. The results showed that : (1) There is no effect of psysical exercise on hemoglobin value (tcount 0.498 < ttabel 1,895). (2) there is a significant effect of psysical exercire with iron suplemen on hemoglobin value (tcount 2.896 > ttabel 1,895). (3) there is a significant different in the effect of physical exercise by physical exercise consumsing iron suplemen on hemoglobin value(tcount 2,152 > ttabel 1,895).